In the stomach of the predators writings and collaborations - Creischer, Alice 1960- (saxpublishers, 2019)
Starting with fictional texts in the mid-1980s, Creischer soon began to write scores for her pioneering performances and, together with her partner Andreas Siekmann, ended up becoming one of the early champions of the second wave of Institutional Critique that formed in the early 90s around Texte zur Kunst and Springerin. A decade later, and often in collaboration with Siekmann, Creischer would begin to expand this institutionally critical grammar towards issues surrounding globalization and transnational structures of exploitation. The twentytwo chronologically ordered essays, poems, performance scores, plays, prose pieces, and critical analyses by the artist, activist, and writer Alice Creischer that are collected in this book aim not only at rendering the manifold transitions of the reunified German (artistic) landscape visible. Moreover, the texts problematize Alice Creischer’s constant struggle for a language to analyze and criticize, to comment and intervene into the socio-economic fabric she finds herself surrounded by.
Impressum: This book is published on the occasion of Alice Creischer's exhibition "I / I can / I cannot / I cannot venture myself", from March 30 to April 21, 2019, at the Miriam and Ira D. Wallach Art Gallery, New York, as an accompanying reader edition of 150 copies
Keywords: Creischer, Alice -- 1960-